2008
DOI: 10.1097/mlg.0b013e31816e2eb7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Occult Nodal Metastases on Survival and Regional Control in Patients With Head and Neck Squamous Cell Carcinoma

Abstract: There is a high incidence of occult metastases in clinically node-negative patients which adversely affects survival, regardless of the use of adjuvant XRT. Postoperative XRT did not significantly affect regional control or survival rates in patients with <3 positive nodes. When ECS was present, survival was poor regardless of the number of nodes. These data emphasize the prognostic and therapeutic role of END and highlight the need for the development of novel therapeutic regimens to improve disease control a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 25 publications
1
52
0
Order By: Relevance
“…Therefore, lymph node status is the most important prognostic factor [56]. SLNB is feasible and reliable and this tumour therefore appears to be a good indication for SLNB [57], especially lesions with moderate or scarce differentiation.…”
Section: Indicationsmentioning
confidence: 98%
“…Therefore, lymph node status is the most important prognostic factor [56]. SLNB is feasible and reliable and this tumour therefore appears to be a good indication for SLNB [57], especially lesions with moderate or scarce differentiation.…”
Section: Indicationsmentioning
confidence: 98%
“…The disease-free survival rate (a) and regional control rate (b) in the cases that were positive for extracapsular spread (ECS); solid lines indicate patients who underwent a surgical treatment at our university hospital and dashed lines indicate patients operated at other institutions. sufficient to warrant PORT, while others [14] have suggested that PORT cannot be recommended unless two or more positive nodes are found. The variability in the proposed indications for PORT raises the following question: should PORT be performed for patients with any histologically positive node or only for patients with more than three nodes?…”
Section: Discussionmentioning
confidence: 96%
“…However, the criteria for neck radiation are not yet well established. There are controversial reports about the benefits of PORT [11][12][13][14]. While some reports suggest that PORT for the neck region improves regional control, other reports suggest the opposite, especially in Nl cases [15][16][17].…”
Section: Introductionmentioning
confidence: 93%
“…8 Also, the diagnosis of node metastases and the presence of extracapsular spread are considered to be an indication for adjuvant treatment. 9 On the other hand, a neck dissection may avoid unnecessary adjuvant treatment and spare the use of radiotherapy.…”
Section: Resultsmentioning
confidence: 99%